Mathematical Model of Electromagnetic Transient for Superconducting Short-Circuit Current Limiter - Manusov V.Z.; Pavlyuchenko D.A.; Miheev P.A. (Problems of the Regional Energetics)
At present on the basis of significant achievements in the field of high-temperature superconductivity more and more applications of this phenomenon appear in the electric power industry, in particular superconducting current limiters. To investigate current limitation process in electrical networks containing superconducting current limiter it is extremely important to evaluate the electrodynamic and thermal effects of the short-circuit current at any time. The existing superconducting current limiters mathematical models don't consider the inertia of the device transition from the superconducting state to the conducting one. It is necessary to develop the mathematical model for the electromagnetic transient process that can adequately simulate the superconducting current limiter at any time point, taking into account its parameters in the normal and emergency modes and also to describe these parameters dynamics during the process of current limitation. The proposed mathematical model allows to simulate the changing inertia of the superconducting current limiter inductive reactance, to analytically describe the electromagnetic transient process, and also to evaluate the electrodynamic and thermal effects of short-circuit current in networks with superconducting current limiter. The important feature of the mathematical model is the consideration of the increase rate (inertia) of the inductive reactance with respect to the external network. Also the model allows taking into account the initial and final values of the inductance of a superconducting current limiter before and after the end of the electromagnetic transient respectively.